DEMOKRASI DAN TRANSPARANSI DALAM PEMILU 2004 - M. Syahbudin Latief (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2009)
This paper is about the process of election during democracy periode in Indonesia. The problem that usually accured during the election was the involvement of the elites in the process of election. Some elites, both from the political parties and from the village, usually interfering the process. The case in Gampeng shows that all elements have been working together in successing the process of election. Reflecting from the election process in Gampeng, the transition process towards more democratic government in Indonesia could be happen inpeace and harmony if there was honesty inside the political elites. They should more appreciate the voice from the people they were represented, instead of fighting for their own needs.